Assessing the residents's preference of awareness regarding urban agriculture at rooftop garden - Jafari, Neda; Mohd Yunus, Mohd.Yazid; Othuman Mydin, Md Azree; Mohd. Tahir, Osman (Trans Tech Publications, 2015)
Roof garden can be used as natural environment in an urban setting. Rooftop agriculture with green roof systems can become an attractive possibility. The aesthetic value of green roofs is considered important in cities where roof escapes are dominated by gray color and unattractive structures. The instant objective of this research was to examine on question: What is the resident’s preference of awareness regarding urban agriculture at rooftop garden? The purpose of this study is to understand the resident’s preference of awareness regarding urban agriculture at rooftop garden. The awareness and potential of rooftop urban agriculture are examined. In this research a method presented quantitative - survey questionnaire distributed among of residents in The Heritage condominium in Selangor and Sri Putramas 2 in Kuala Lumpur. The result is expected to lead towards cognition and awareness to elevate sustainable building and promoting the usage of urban agriculture at rooftop gardening residential building. In conclusion of this research contain the result of survey questionnaire that related to awareness of urban agriculture at rooftop garden who residents take part in the survey are agree with this section. Furthermore, this study help to residents for receive a perfect environmental in their live area.